To live or let die: Unclear task of autophagy in the radiosensitization battle - Ondrej, Martin; Cechakova, Lucie; Durisova, Kamila; Pejchal, Jaroslav; Tichy, Ales (Radiotherapy and oncology, 2016)
Radiation-induced autophagy is believed to represent a radioprotective mechanism of cancer cells. Thus, its inhibition should support radiation treatment and increase its efficacy. On the other hand, there is evidence that radiation alone or in combination with various chemical agents can induce autophagy that results into increased cell death, especially within transformed apoptosis-resistant cells. In this paper, besides description of autophagic process and its relation to cancer and radiotherapy, we compared two contradictory radiosensitization approaches that employ inhibition and induction of autophagy. In spite of the classical concept based on cytoprotective model, there is a plethora of recently developed inducers of autophagy, which indicates the future trend in radiosensitization via modulation of autophagy. Because contemporary literature is conflicting and inconsistent in this respect, we reviewed the recent studies focused on enhancement of sensitivity of cancer cells toward radiation in regard to autophagy, revealing some striking discrepancies. The deeper the knowledge, the more complex this situation is. To interpret results of various studies correctly one has to take into account the methodology of autophagy assessment and also the fact that radiosensitization might be mediated by other than intrinsic mechanisms related to autophagy. Notwithstanding, targeting autophagy remains an attractive anti-tumor strategy.
Keywords: autofagie; Radiotherapy; lidé; Radiosensitization; ATM protein; Humans; chlorochin; Autophagy; Phosphatidylinositol 3-Kinases; Cell Hypoxia; Ionizing radiation; nádory; membránové proteiny; hypoxie buňky; protoonkogenní proteiny; Inhibition; fosfatidylinositol-3-kinasy; Membrane Proteins; Induction; tolerance záření; Neoplasms; Ataxia Telangiectasia Mutated Proteins; Radiation Tolerance; Chloroquine; Proto-Oncogene Proteins